Early Detection and Good Team Collaboration for Preventing Maternal Death Caused by Placenta Accreta Spectrum Disorder - Yuliantara, Eric Edwin; Bachnas, Muhammad Adrianes; Anggraini, Nutria Widya Purna; Prabowo, Wisnu; Nugraha, Gagah Baskara Adi; Chasanah, Meriska Dewi; Alim, Fadel Muhammad S.; Merina, Hikmah F. (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Placenta accreta spectrum (PAS) is considered one of the most harmful pregnancy conditions, as it is strongly linked with maternal morbidity and mortality. An accurate and early prenatal diagnosis of PAS allows time for a multidisciplinary team to plan the best course of action for delivery management. The aim of this study is to describe placenta accreta spectrum management and outcomes with early detection and a multidisciplinary team approach.Method: A retrospective cohort study was conducted on 167 cases of placenta accreta from 2016 to 2021. Medical records were then reviewed, and data were collected for delivery management and maternal outcome, including estimated amounts of bleeding, urinary tract injury, delivery time, ICU referral, and maternal death.Result: Delivery management (hysterectomy and conservative management) and maternal bleeding were significantly associated with MAP score (p < 0.05), while urinary tract injury, delivery time, ICU admission, and maternal death were not significantly associated (p > 0.05). 55.1% of patients underwent hysterectomy, and the rest 44.9% underwent conservative surgery. Massive bleeding of more than 2500 mL happened in 54.5% of patients, and the rest 45.5% managed to bleed less than 45.5%. Preterm deliveries accounted for 29.9% of all deliveries, with the remaining 70.1% being term. 5.4% of patients experienced urinary tract injuries. 6.6% of patients were referred to the intensive care unit. The maternal mortality rate is 4.8%.Conclusion: Early detection of the placenta accreta spectrum, as well as good collaboration among members of a multidisciplinary team from various medical fields, are required to ensure the mother and baby's safety and survival.